2011
DOI: 10.1097/ncc.0b013e31820a5943
|View full text |Cite
|
Sign up to set email alerts
|

High Perceived Stress Is Linked to Afternoon Cortisol Levels and Greater Symptom Distress in Patients With Localized Prostate Cancer

Abstract: Patients treated for prostate cancer with RP or RT should be assessed for symptoms and symptom distress and targeted for early symptom management interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The symptoms and related distress in the area of sexual functioning were perceived to be a greater problem than symptoms and distress related to urinary and bowel problems (Hsiao et al . ). In addition, symptom‐related distress was significantly associated with perceived stress (Hsiao et al .…”
Section: Introductionmentioning
confidence: 97%
“…The symptoms and related distress in the area of sexual functioning were perceived to be a greater problem than symptoms and distress related to urinary and bowel problems (Hsiao et al . ). In addition, symptom‐related distress was significantly associated with perceived stress (Hsiao et al .…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have reported significant associations between perceived stress and overall quality of life in mixed cancer groups18 and in men with localised prostate cancer1920. In the emotional domain, Hsaoi et al21 found a significant association between global perceived stress and greater prostate cancer symptom distress one to three months post treatment and stress appraisal predicted total mood disturbance in a group of men two years post treatment22. While research in this area is limited, the evidence suggests a link between perceived stress and later psychological adjustment.…”
mentioning
confidence: 99%
“…The association between increasing relationship commitment and reduced T levels in men confirms and extends prior research linking T with mating effort, whereas another study suggests that T does not vary with relationship quality or commitment in monogamous, heterosexual women (Hooper et al, 2011). Hsiao et al (2011) has recently suggested that perceived stress was positively correlated with higher afternoon cortisol levels and greater symptoms of distress. It is presently unknown how exactly cortisol covaries with T in relation to fatherhood or relationship status in men.…”
Section: Discussionmentioning
confidence: 99%